2017
DOI: 10.1111/issr.12151
|View full text |Cite
|
Sign up to set email alerts
|

Ensuring inclusion and combatting discrimination in social protection programmes: The role of human rights standards

Abstract: Recent years have witnessed the significant expansion of social protection programmes around the world. Yet, a vast number of poor and vulnerable people, including children, women, ethnic minorities, and persons with disabilities, remain uncovered, especially in lower-income countries. This article argues that a better understanding of the principle of equality and non-discrimination, as defined under international human rights law, can guide practitioners and policy-makers to design and implement more inclusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…The third main approach we identified suggests that social protection systems should align with human rights principles. Sepúlveda Carmona (2017) argues that the principles of equality and non-discrimination can be better utilized to overcome wide and persistent coverage gaps for women, including through application to various system components and mechanisms such as personal identification systems and targeting mechanisms. In South Africa, Matthews (2020) applies a human rights perspective to the conceptualization and implementation of the national social protection system as it interacts with labour policy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The third main approach we identified suggests that social protection systems should align with human rights principles. Sepúlveda Carmona (2017) argues that the principles of equality and non-discrimination can be better utilized to overcome wide and persistent coverage gaps for women, including through application to various system components and mechanisms such as personal identification systems and targeting mechanisms. In South Africa, Matthews (2020) applies a human rights perspective to the conceptualization and implementation of the national social protection system as it interacts with labour policy.…”
Section: Resultsmentioning
confidence: 99%
“…In South Africa, Matthews (2020) found that the adoption of a digital identification system during the COVID-19 pandemic exposed Black South African women to predatory creditors. Challenges also exist in ensuring equitable access when benefits are dispersed through digital means, for example with cash transfers delivered via mobile phones in contexts where women’s technology ownership is low, or with fingerprint technologies that for example do not pick up prints on hands that are worn through age or manual labour (Sepúlveda Carmona, 2017). Barca et al (2021) suggest that while digital information systems can be leveraged to decrease the risk of gender- and disability-related exclusion throughout the social protection delivery chain, the technology on its own will not generate inclusion–it needs to be designed in service of inclusive goals.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the normative level, social protection is enshrined as a human right in the Universal Declaration of Human Rights and the two Covenants on Economic, Social and Cultural Rights and Civil and Political Rights, and more recently in the UN 2030 Agenda. Where social protection policy is deducted from a social contract, the state has an obligation towards its citizens to deliver equitable access to social services or to facilitate access to employment and incomes (Sepúlveda Carmona 2017;Kabeer 2005;). Historically, many countries have commitments to a welfare state or social contract in their constitutions.…”
Section: Conceptual Framings Of Social Inclusion Trust and Social Coh...mentioning
confidence: 99%
“…The transaction costs in time and expenditure connected to retrieving a social protection benefit may lock out those recipients with the most urgent need for support. Other obstacles include cultural and language barriers, or technology-related barriers, such as accessing a paypoint (Sepúlveda Carmona 2017). Gender-related social norms and intersecting inequalities can severely jeopardize access to a scheme, place additional work burdens on women and girls and put them at risk (Chopra and Campos Ugalde 2018;Razavi 2011;Sepúlveda Carmona 2017).…”
Section: The Role Of Delivery and Accountability Mechanismsmentioning
confidence: 99%
“…Racially inspired human rights violations contribute to the complexity in humanitarian contexts and it is recognised by international human rights law ( Bantekas, 2020 ) and protested against through the BLM movement. As a public emergency, human rights violations perpetuate negative consequences on civic space and human rights as well as creating additional barriers for already excluded groups ( Sepúlveda Carmona, 2017 ). Using force to shut down the freedom of expression during these events is another form of human rights violations ( Anisin, 2016 ).…”
Section: Exploring Contemporary Complex Humanitarian Crisis Driversmentioning
confidence: 99%